Comparison of 6-[(18)F]-fluorodopamine positron emission tomography to [(123)I]-metaiodobenzylguanidine and [(111)In]-pentetreotide scintigraphy in the localization of non-metastatic and metastatic pheochromocytoma - Ilias, Ioannis (2008)
We compared functional imaging modalities including positron emission tomography (PET) with 6-[(18)F]-fluorodopamine ([(18)F]-DA) against [(123)I]-metaiodobenzylguanidine ([(123)I]-MIBG) and somatostatin receptor scintigraphy (SRS) with [(111)In]-pentetreotide (Octreoscan) in non-metastatic and metastatic pheochromocytoma (PHEO). Methods: We studied 25 men and 28 women (mean age±SD: 44.2±14.2 years) with biochemically-proven non-metastatic (n: 17) or metastatic (n: 36) PHEO. Evaluation included anatomical imaging with computed tomography (CT) and/or magnetic resonance imaging (MRI) and functional imaging that included at least two nuclear medicine modalities: [(18)F]-DA PET, [(123)I]-MIBG scintigraphy, or SRS. Sensitivity of functional imaging vs. anatomical imaging was assessed on a per-patient and on a per-region basis. RESULTS: For this available cohort, on a per patient basis, overall sensitivity (combined for non-metastatic and metastatic PHEO) was 90.2% for [(18)F]-DA PET, 76.0% for [(123)I]-MIBG scintigraphy, and 22.0% for SRS. On a per-region basis, overall sensitivity was 75.4% for [(18)F]-DA PET, 63.4% for [(123)I]-MIBG scintigraphy, and 64.0% for SRS. CONCLUSION: If available, [(18)F]-DA PET should be used in the evaluation of PHEO, since it is more sensitive than [(123)I]-MIBG scintigraphy or SRS. If [(18)F]-DA PET is not available, [(123)I]-MIBG scintigraphy (for non-metastatic/adrenal PHEO) and SRS (for metastatic PHEO) should be the first alternative imaging methods to be used.